2020
DOI: 10.1108/imefm-04-2019-0135
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of capital structure of banks: evidence from the Kingdom of Saudi Arabia

Abstract: Purpose The purpose of this study is to investigate the most important factors that affect the capital structure of commercial banks in the Kingdom of Saudi Arabia. Design/methodology/approach This study uses annual data of 11 Saudi commercial, national banks listed on the tadawul Saudi stock exchange for the period 2010–2017. Data was collected from the banks financial statements, tadawul annual publications and Saudi Arabian Monetary Authority. By constructing a balanced panel, this study uses pooled ordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
56
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 61 publications
(128 reference statements)
12
56
2
3
Order By: Relevance
“…The greater the size of the company will increase the agency cost due to the asymmetric information that arises. This result contradicts the findings of Al-Hunnayan (2020); Bukair (2019); Etudaiye-Muhtar and Abdul-Baki (2020); Guizani and Ajmi (2021); Kahya et al (2020); Khan et al (2020), stating that in Islamic banking in the Middle East and developing countries, SIZE had a positive and significant effect. In this study, the Non-debt tax shield (NDTS) had no significant effect on STD.…”
Section: Variablecontrasting
confidence: 71%
See 3 more Smart Citations
“…The greater the size of the company will increase the agency cost due to the asymmetric information that arises. This result contradicts the findings of Al-Hunnayan (2020); Bukair (2019); Etudaiye-Muhtar and Abdul-Baki (2020); Guizani and Ajmi (2021); Kahya et al (2020); Khan et al (2020), stating that in Islamic banking in the Middle East and developing countries, SIZE had a positive and significant effect. In this study, the Non-debt tax shield (NDTS) had no significant effect on STD.…”
Section: Variablecontrasting
confidence: 71%
“…Thus, H1 is generally accepted. In most studies on capital structure in the banking sector, researchers find that the level of profitability has a negative effect on the capital structure (Al-Hunnayan, 2020;Ghosh & Chatterjee, 2018;Guizani & Ajmi, 2021;Kahya et al, 2020;Khan et al, 2020). However, several studies have found that the profitability of banking companies has a positive and significant effect on their debt structure (Etudaiye-Muhtar& Abdul-Baki, 2020).…”
Section: Hypothesis Testing and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There existed some mixed outcomes regarding this area of the stated determinant. Some shreds of evidence uncovered a noteworthy positive association between size and leverage (Al-Hunnayan, 2020;Amidu, 2007;Anarfo, 2015;Bukair, 2019;Heider & Gropp, 2008;Khan et al, 2020;Kuč & Kaličanin, 2020;Manos & Ah-Hen, 2003;M'ng et al, 2017;Oino, 2014;Režňáková et al, 2010;Shah & Jam-e-Kausar, 2012;Sheikh & Qureshi, 2017;Ukaegbu & Voulgaris et al, 2004), conversely, there existed some significant negative impacts of size on leverage (Güner, 2016;Handoo & Sharma, 2014;Kayo & Kimura, 2011;Khan et al, 2020;and Sharif & Muhammad, 2019). In addition, some studies uncovered that there were no significant impacts of size on leverage (Islam, 2016;and Ullah et al, 2017).…”
Section: Bank Sizementioning
confidence: 99%